The Effect of Message Frames on Attitudes Toward Internationalizing Agricultural Extension - Lisa K. Lundy (Journal of Applied Communications, 2007)
This study examines to what extent alternative message frames are capable of influencing attitudes for an internal organizatjonal communication message. Communicators proposed framing messages to persuade internal audiences about the benefits of internationalization for their organizations. In this applied communication context, framing was situated within the Elaboration Likelihood Model (ELM) of persuasion. Overall, the findings suggested that the psychological indicator of issue involvement was more strongly related to attitudes toward internationalizing Extension than the message frames presented. However, results indicate there is potential for alternative message frames to influence attitudes toward organizational initiatives.